Bronchiolitis obliterans associated with toxic epidermal necrolysis induced by infection: A case report and literature review - Liu, Jingwei; Yan, Haibo; Yang, Chunfeng; Li, Yumei (Frontiers in Pediatrics, 2023)
Background: Stevens-Johnson syndrome/toxic epidermal necrolysis has a severe impact on patients’ eyes, genital mucosa, and many other organs. Bronchiolitis obliterans is a rare complication of Stevens-Johnson syndrome /toxic epidermal necrolysis. Data sources: We report a case of bronchiolitis obliterans associated with toxic epidermal necrolysis in our department. Furthermore, we examined the patients with bronchiolitis obliterans induced by Stevens-Johnson syndrome/toxic epidermal necrolysis and summarized the clinical characteristics, treatment and prognosis. Databases available online in English including PubMed, Medline and Web of Science were consulted. Results：We report one case and review 23 published case reports. In the 24 patients, 13 were female, and the oldest patient was 59 years old and the youngest was 5 years old. The time of bronchiolitis obliterans onset after Stevens-Johnson syndrome /toxic epidermal necrolysis varied from 5 days to 5 months. Bronchoscopy examination showed ulceration，exudative lesions, occlusion and inflammation. The CT of lung manifestation included mosaic perfusion, bronchiectasis, consolidation, air trapping, pneumatocele, pleural thickening, lung collapse, larger central airway dilatation, lung over inflation, oligemia and pneumomediastinum. Most cases indicated pulmonary function tests with obstructive ventilation dysfunction. The prognosis was poor; six patients were dead. Conclusions: Patients with Stevens-Johnson syndrome / toxic epidermal necrolysis may develop bronchitis obliterans at different stages, so all patients with Stevens-Johnson syndrome / toxic epidermal necrolysis should be followed up for possible respiratory complications.